2005
DOI: 10.1243/095765005x69233
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of an aqueous desiccant mixture system: Air dehumidification and desiccant regeneration

Abstract: This article presents the results of an experimental study on the performance of a structured packing dehumidifier and the regenerator system. The system is tested using different proportions of an aqueous desiccant mixture of calcium chloride and lithium chloride solutions with an overall concentration of 40 wt%. The instantaneous effectiveness and the time-average effectiveness of the dehumidification process as well as the regeneration process are defined for the hybrid cooling system. It is found that as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Dai et al [7] experimentally investigated a hybrid LDAC system comprised of a VCS, a liquid desiccant system, and an evaporative cooler, and the COP was found to be 1.513, 1.862, and 1.745 while using VCS, VCS + desiccant dehumidification, and VCS + desiccant dehumidification + evaporative cooling, respectively. Al-Farayedhi et al [8] suggested a system consisting of a packed-bed dehumidifier with a five-ton capacity VCS while employing CaCl 2 as liquid desiccant, and results revealed that temperature of the air was reduced from 48 to 38 • C and the value of outlet-to-inlet absolute humidity was found to be 0.6. The COP hybrid was calculated in three different regeneration modes: 1.164 (while heating desiccant), 1.616 (while heating air), and 1.4221 (while heating both air and desiccant), and the COP of the standalone VCS was 0.989.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al [7] experimentally investigated a hybrid LDAC system comprised of a VCS, a liquid desiccant system, and an evaporative cooler, and the COP was found to be 1.513, 1.862, and 1.745 while using VCS, VCS + desiccant dehumidification, and VCS + desiccant dehumidification + evaporative cooling, respectively. Al-Farayedhi et al [8] suggested a system consisting of a packed-bed dehumidifier with a five-ton capacity VCS while employing CaCl 2 as liquid desiccant, and results revealed that temperature of the air was reduced from 48 to 38 • C and the value of outlet-to-inlet absolute humidity was found to be 0.6. The COP hybrid was calculated in three different regeneration modes: 1.164 (while heating desiccant), 1.616 (while heating air), and 1.4221 (while heating both air and desiccant), and the COP of the standalone VCS was 0.989.…”
Section: Introductionmentioning
confidence: 99%